(untitled) (Texas Journal of Medical Science, 2025)
The purpose of this study was to investigate the relationships between allelic variants of acetylation and the blood lipid profile in patients with chronic periodontitis associated with hepatitis C. Biochemical studies were conducted on 42 individuals aged 18–45 years (24 men and 18 women) diagnosed with chronic periodontitis associated with chronic hepatitis C. The acetylation phenotype in saliva and the blood lipid spectrum were studied. A higher prevalence of the disease was noted among patients with a slow acetylation phenotype in saliva, averaging 17% in the primary group. Patients with a slow acetylation phenotype demonstrated elevated triglyceride levels, which were accompanied by lower concentrations of cholesterol, high-density lipoproteins (HDL), and low-density lipoproteins (LDL) in the blood.